Child Well-Being in Times of Confinement: The Impact of Dialogic Literary Gatherings Transferred to Homes - Ruiz-Eugenio, Laura; Roca-Campos, Esther; León-Jiménez, Susana; Ramis-Salas, Mimar (Frontiers in Psychology, 2020)
COVID-19 pandemic has supposed an unexpected situation that has forced to find educational alternatives to support learning and ensure child well-being. The need for practices that “open doors” at home as a way to promote a quality education and to foster an environment of supportive relationships and a sense of community, has led to the in-depth analysis of successful educational actions, particularly the Dialogic Literary Gatherings (DLGs). The aim of this article is to show how the transference of DLGs to the home environment has had an impact in child subjective well-being in times of confinement, promoting a safe and supportive environment for learning, interacting, coexisting and for the emotional development in different educational stages, especially for the most vulnerable children. Data collection consisted of a focus group of 10 teachers, 6 semi-structured interviews addressed to families and 6 life stories of students, from 4 primary education centres, 1 high school and 1 Special Education School. Communicative methodology structured the two-level data analysis, for studying both the elements provided by online DLGs that favour and achieve child well-being, and the elements that may hinder those achievements. The results confirm that DLGs have supposed a notorious impact on children’s and their families’ well-being. Considering the findings in the development of educational public policies, the possibility of extending “open doors actions” as an option for future learning environments beyond the confinement situation is contemplated. Future research on how these spaces can have an impact on child well-being in upcoming contexts of the new normal in the education domain will be of interest.